Factors Associated with the Completeness of Inpatient Medical Record Filling - Mohammed Talal Alhammadi , Ahmed Ali Ahmed Alghamdi , Khalid Othman haris alzahrani , Noof Owayed Alanazi , Maryam Mohmmed Ali Al Sayar , Fatimah Ahmad Mohammad Albar , Khalid Mohmmed Mothagab Qohal; Rana Hassan Ali Hakami , Ghada Abdo Taher Habbash , Saad Abdulrahman Saad Bin Hameed , Khulud Turki Alanzi (Migration Letters, 2022)
Background: The incompleteness of medical record (MR) documents is a problem because medical records are often the only records that can provide detailed information about what has happened while the patient was treated. MR is vital to all patient healthcare activities. Basically, they form part of a doctor’s ethical and legal duty in providing good patient care. Respectable quality medical records, including completeness of record filling, are essential to proper ongoing care of the patient and are dominant for effective communication between healthcare professionals and their patients. However, studies in KSA examining factors associated with the completeness of inpatient medical record filling is scanty. The study aims: To examine factors associated with the completeness of inpatient medical record filling in a hospital. Method: A cross-sectional design was conducted at hospital, Jeddah, KSA from January to May 2022. A total of 213 nurses working at the inpatient service ward were selected for this study by proportional random sampling, composing of 115 nurses with graduate degree and 35 nurses with diploma degree. The dependent variable was completeness of inpatient medical record filling. The independent variables were education level, employment status, tenure, responsibility, and organization support. The data were collected by questionnaire and document review. The data were analyzed by a multiple logistic regression. Results: Completeness of inpatient medical record filling was positively associated with higher education (OR= 2.94; CI 95%= 1.08 to 8.00; p= 0.034), civil servant status of employment (OR= 4.01; CI 95%= 1.71 to 9.40; p=0.001), ≥ 3 year tenure (OR= 8.84; CI 95%= 2.78 to 28.16; p<0.001), higher knowledge (OR= 5.37; CI 95%= 1.40 to 20.55; p=0.014), stronger responsibility (OR= 3.13; CI 95%= 1.35 to 7.28; p=0.008), and stronger organizational support (OR= 4.08; CI 95%= 1.72 to 9.67; p=0.001). Conclusion: Completeness of inpatient medical record filling is positively associated with higher education, civil servant status of employment, ≥3 year tenure, higher knowledge, stronger responsibility, and stronger organizational support.